2016
DOI: 10.1111/dom.12738
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial comparing basal insulin peglispro and insulin glargine, in combination with prandial insulin lispro, in patients with type 1 diabetes: IMAGINE 1

Abstract: Aims: The primary objective was to demonstrate that basal insulin peglispro (BIL) was noninferior compared with insulin glargine (GL) for haemoglobin A1c (HbA1c) at 26 weeks with a non-inferiority margin of 0.4%. Results: At 26 weeks, mean HbA1c was 7.06% AE 0.04% and 7.43% AE 0.06% for patients assigned to BIL (N = 295) and GL (N = 160), respectively (difference -0.37% [95% CI: −0.50 to −0.23], P < .001); more patients on BIL achieved HbA1c <7% (44.9% vs 27.5%, P < .001). Compared with GL, patients using BIL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(71 citation statements)
references
References 24 publications
(57 reference statements)
7
64
0
Order By: Relevance
“…In this study, LS mean HbA1c after 12 weeks (6.8%) and 36 weeks (7.0%) of therapy is comparable to the BIL‐treated patients in other T1D trials: 7.1% and 7.4%, respectively, at 26 and 78 weeks in IMAGINE 1 ( n = 295) and 7.4% at 52 weeks in IMAGINE 3 ( n = 664) . Finally, the observations of the lipid changes and increases in ALT and AST in this study are consistent with changes observed in studies of comparing BIL to conventional insulins in patients previously treated with insulin . Each of these variables returned to baseline or near baseline during the 4 weeks off study drug in this and previous studies …”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In this study, LS mean HbA1c after 12 weeks (6.8%) and 36 weeks (7.0%) of therapy is comparable to the BIL‐treated patients in other T1D trials: 7.1% and 7.4%, respectively, at 26 and 78 weeks in IMAGINE 1 ( n = 295) and 7.4% at 52 weeks in IMAGINE 3 ( n = 664) . Finally, the observations of the lipid changes and increases in ALT and AST in this study are consistent with changes observed in studies of comparing BIL to conventional insulins in patients previously treated with insulin . Each of these variables returned to baseline or near baseline during the 4 weeks off study drug in this and previous studies …”
Section: Discussionsupporting
confidence: 89%
“…These data are consistent with what would be expected of the long half‐life observed for BIL in PK studies . Furthermore, in other studies, glycaemic variability was lower with BIL than with comparator insulins (insulin glargine and NPH) . Reduction of glycaemic variability may not only allow more effective titration of basal insulin and improved glycaemic efficacy compared to insulin glargine or NPH but may also reduce nocturnal hypoglycaemia and perhaps reduce the risk or delay the onset of long‐term health concerns .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations